Long non-coding RNA ANRIL polymorphisms in papillary thyroid cancer and its severity. Issue 2 (3rd April 2021) - Maruei-Milan, R; Heidari, Z; Aryan, A; Asadi-Tarani, M; Salimi, S
ABSTRACT: Background : Long non-coding RNAs are likely to have a role in the pathogenesis of many diseases, including cancer. We hypothesised an effect of certain ANRIL single nucleotide polymorphisms (SNPs) in papillary thyroid cancer. Methods : Genomic ANRIL SNPs in rs11333048, rs4977574, rs1333040 and rs10757274 were determined in 134 papillary thyroid cancer patients and 155 age- and sex-matched controls. Results : None of the ANRIL SNPs were individually linked to papillary thyroid cancer. However, the AAAC haplotype (A from rs11333048, A from rs4977574, A from rs1333040 and C from rs10757274, respectively) showed a protective effect from papillary thyroid cancer whilst the CAAC and CAGT haplotypes were associated with cancer. The rs1333048 CC variant was more frequent in patients with larger tumour size (≥1 cm) in a recessive model (OR 3.4 [95%CI, 1.1–11], P = 0.035). The rs4977574 AC variant was associated with smaller tumour size in an over-dominant model (OR 0.4 [95%CI, 0.2–1.0], P = 0.041). SNPs in rs10757274 (AA: p = 0.045) and rs1333040 (CC: p = 0.019) are linked to a lower likelihood of III–IV cancer stages in dominant or codominant models. Conclusions : Certain haplotypes of ANRIL SNPs are associated with papillary thyroid cancer. ANRIL rs1333048 and rs4977574 variants were associated with larger and smaller tumour sizes, respectively. rs10757274 and rs1333040 variants might lead to lower III–IV cancer stages. These SNPs may be important in the diagnosis of this form of thyroid cancer.